«The flow of the market in society» as a political issue - S. G. Kara-Murza (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
The author reveals the political base of the liquidation process of the economic system and social system of the Soviet Union, which was contrary to the logic of economic science and the recommendations of the famous foreign economists. The author gives the characteristic of the threats generated by the dictates of the market and analyzes the fate of the Russian intelligentsia, which did not stand under the «pressure of the market economy».